Business Cycles and Start-ups across Industries: An Empirical Analysis of German Regions - Alexander Konon; Michael Fritsch; Alexander S. Kritikos (Institute of Labor Economics (IZA), 2018)
We analyze whether start-up rates in different industries systematically change with business cycle variables. Using a unique data set at the industry level, we mostly find correlations that are consistent with counter-cyclical influences of the business cycle on entries in both innovative and non-innovative industries. Entries into the large-scale industries, including the innovative part of manufacturing, are only influenced by changes in the cyclical component of unemployment, while entries into small-scale industries, like knowledge intensive services, are mostly influenced by changes in the cyclical component of GDP. Thus, our analysis suggests that favorable conditions in terms of high GDP might not be germane for start-ups. Given that both innovative and non-innovative businesses react counter-cyclically in 'regular' recessions, business formation may have a stabilizing effect on the economy.
Keywords: E32; L16; L26; R11; 330; new business formation; entrepreneurship; business cycle; manufacturing; services; innovative industries